PREDICTING BANKRUPTCY OF THE ENTERPRISE AND FINSIM_PRO2018 SIMULATION MODEL IN THE STUDY PROCESS (Globalization and Business, 2023)
Financial Statement of the Organization for Financial Reporting Analysis The main objective of any economic process, including financial analysis, is the first: to identify the reasons for the financial stability of the organization and to set  the  measurements  to  eliminate  them;  Second,  in  case  of maintaining existing tendencies of the enterprise, the prediction about the expected results; On the basis of modeling, find ways and means of ensuring financial sustainability. The article describes the FINSIM_PRO2018 simulator created by our financial statements.